Socio-demographic and clinical profile of substance abuse patients admitted to an emergency department in Ankara, Turkey - Avci, Sema; Sarikaya, Ridvan; Kavak, Nezih; Özmen, Fatma Nihal; Aydin, Macit; Arslan, Engin Deniz; Büyükcam, Fatih (Acta Biomedica Atenei Parmensis, 2017)
Background: Illicit drug abuse is an important health problem around the world. Cannabis is the most commonly used illicit drug, followed by amphetamines, opioids, and cocaine. In this study, we searched the socio-demographic features of drug abusers admitted to an emergency department. Materials and methods: The study was performed in the emergency department of an education and training hospital in Ankara, Turkey. The socio-demographic features, substances commonly consumed, and the reason for the patients’ presentation were recorded. Results: The mean age of patients was 28.3±9.2. Of those under study, 93.3% were male; 68.7% were discharged from the emergency department after a short observation period; and 10.4% were hospitalized. The median age of the patients’ first experience with illicit substances was 19 (4-56). Conclusion: Illicit drug use remains a significant medical health problem, not only in Turkey but also around the world. Abusers frequently seek emergency services, complaining of various symptoms, but generally do not mention their substance abuse. Emergency physicians must ask patients if they use abuse drugs.